PRESEVATION OF COTTON FISH NET TWINES BY TANNING : I. OPTIMUM CONCENTRATION OF TANNING BATH - CECILY, (Smt.) P. J; KUNJAPPAN, M K. (Fishery Technology, 2025)
Samples of tannin-containing preservatives used by fishermen lin India for treating cotton nets were collected and qualitative and quantitative characterisation of the tannins made. The concentrations of different tannins required to impart optimum periods of preservation to the net were worked out and found to be 2% in 8 out of 10 materiaJs studied.